T&T Clark reader in Edward Schillebeeckx - Erp, Stephan van 1966-; Minch, Daniel 1986- (T&T Clark, 2023)
"This reader shows why Edward Schillebeeckx remains one of the most influential Catholic theologians of the 20th century. Spanning more than half a century and including several texts that appear in English for the first time, it enables students to understand how Edward Schillebeeckx' thought resonates with current debates in theology, for instance on ecology and secularization. T&T Clark Reader in Edward Schillebeeckx includes selections from both pre- and post-Conciliar texts that illustrate the evolution in Schillebeeckx's thought, while also pointing towards the deep underlying continuity which comes from his essential commitment to his faith. His Christological Trilogy, which was a touchstone for doctrinal controversy and methodological progress, is represented here, as well as important works on ministry, the sacraments, hermeneutics, secularization, and the environment. These complex theological topics are broken down in every chapter with the help of explanatory notes, discussion questions and further reading suggestions. This reader is an essential resource which will enable students to contextualize and unpack the rich layers within Schillebeeckx's theology."
Includes bibliographical references and index
Keywords: Schillebeeckx, Edward -- 1914-2009; Catholic Church / Doctrines / History